Feasibility Of Making Concrete Using Lignite Coal Bottom Ash As Fine Aggregate - Thandavamoorthy T. S. (Archives of Civil Engineering, 2015)
Concrete is generally produced using materials such as crushed stone and river sand to the extent of about 80-90% combined with cement and water. These materials are quarried from natural sources. Their depletion will cause strain on the environment. To prevent this, bottom ash produced at thermal power plants by burning of coal has been utilized in this investigation into making concrete. The experimental investigation presents the development of concrete containing lignite coal bottom ash as fine aggregate in various percentages of 25, 50, and 100. Compressive, split tensile, and flexural strength as part of mechanical properties; acid, sulphate attack, and sustainability under elevated temperature as part of durability properties, were determined. These properties were compared with that of normal concrete. It was concluded from this investigation that bottom ash to an extent of 25% can be substituted in place of river sand in the production of concrete.